Work engagement among school directors and teachers' behavior at work - Gamero-Burón, Carlos; Lassibille, Gérard (My University, 2017)
The purpose of this paper is to analyze engagement at work among public primary school directors and to investigate the impact of school heads' management style on teachers' behavior at work, in a developing country. Results are based on a specific survey of workflow processes and a representative sample of around 1,000 public primary schools in Madagascar. These surveys gather extremely rare information on several aspects of the staff’s behavior at work and on the tasks performed as part of their workflow. Two-levels models and least square models are used to analyze engagement at work among school directors, and to evaluate the impact of school director's management style on teachers' engagement at work. Findings indicate that many aspects of the pedagogical process are poorly managed and that far too many administrators neglect tasks deemed essential for student learning. Although every school leader is different, successful or engaged school leaders share key characteristics. In this regards, the results clearly show that principals who are highly committed to their work are more likely to hold a permanent contract, to be satisfied with their job, to have a dual role of teacher and administrator, and, to a lesser extent, to work in schools with good physical conditions. As far as teachers' conscientiousness is concerned, school leaders do matter. It is found that principal’s management style has a significant and positive impact on teachers’ behavior at work and a central role to play in developing effective schools. To our knowledge, this paper is the first to investigate school leadership practices in an African setting. In addressing these questions, the paper contributes to the current base of knowledge on education quality and provides insightful lessons for the development of policies that seek to improve the management of primary schools in low-income countries.
Keywords: Enseñanza primaria; Work engagement; School heads; Primary education; Madagascar